Collage (die); Geschichte eines künstlerischen Ausdruckmittels. - Wescher, H. (Köln : DuMont Buchverlag, 1968)
de Achevedo, Adelia ; Agar, Eileen ; de Alarçon, Pedro Antonio ; Albers, Josef ; Alcopley, Lewin ; Alexandra, Barbara ; Altman, Natan ; Andersen, Hans Christian ; Andreenko, Michel ; Annenkoff, Jurij ; Aragon, Louis ; Archipenko, Alexander ; Arenas, Braulio ; Arensberg, Walter ; Arman ; Arnaud, Noël ; Arp, Hans (Jean) ; Atkins, Anna ; Auric, Georges ; Baader, Johannes ; Baargeld, Johannes Theodor ; Baj, Enrico ; Ball, Hugo ; Balla, Giacomo ; Banting, John ; Baranoff-Rossine, Wladimir ; Bardi, P.M. ; Barnes, A. ; Barta ; Bartók, Béla ; Barzun, H. ; Bauer, Rudolf ; Baumeister, Willi ; Baxter, Robert ; Bayer, Herbert ; Baziotes, William ; Beardsley, Aubrey ; Behne, Adolf ; Behrens, Peter ; Bellioli, Carlo ; Bellmer, Hans ; Benes, V. ; Bergmann-Michel, Ella ; Berlewi, Henryk ; Berman, Mieczyslaw ; Berni, Antonio ; Bettencourt, Pierre ; Biebl ; Biedermann ; Bill, Max ; Bille, Ejler ; Billy, André ; Birot, Pierre-Albert ; Bjerke-Petersen, W. ; Blake, Peter ; Blum, René ; Blumenfeld, Erwin ; Boccioni, Umberto ; Böcklin, Arnold ; Bolotowsky, Ilya ; Bonnard, Pierre ; Borisoglebskij, M. ; Bortnik, Alexandr ; Boumeester, Christine ; Bourdelle, Antoine ; Bragaglia, A.G. ; Brancusi, Constantin ; Braque, Georges ; Brauner, Victor ; Brenner ; Breton, André ; Breton, Jacqueline Lamba ; Brignoni, Sergi ; Brik, Lili ; Bronstein, Max ; Browne, Byron ; Brucz, Stanislaw ; Bruni, L. ; Brunius, J.B. ; Bryen, Camille ; Bucaille, Max ; Buchet, Gustave ; Buchheister, Carl ; Buchholz, Erich ; Buguslawskaja, Xenia ; Bunuel, Luis ; Burchard, Otto ; Burchartz, Max ; Burljuk, Vladimir Davidovic ; Burra, Edward ; Burri, Alberto ; Busch, Paul ; Buscher, Alma ; Busoni, Ferruccio ; Buzzi ; Cáceres, Jorge ; Cahn, Gustave ; Calder, Alexander ; Cangiullo, F. ; Canis, J. ; Cant, J. ; etc.
boek